Review of Large-Scale Biochar Field-Trials for Soil Amendment and the Observed Influences on Crop Yield Variations - Vijay, Vandit; Shreedhar, Sowmya; Adlak, Komalkant; Payyanad, Sachin; Sreedharan, Vandana; Gopi, Girigan; Sophia van der Voort, Tessa; Malarvizhi, P; Yi, Susan; Gebert, Julia; Aravind, PV (Frontiers in Energy Research, 2021)
Increasing pressure on farming systems due to rapid urbanization and population growth has severely affected soil health and fertility. The need to meet the growing food demands has also led to unsustainable farming practices with the intensive application of chemical fertilizers and pesticides, resulting in significant greenhouse gas emissions. Biochar, a multifunctional carbon material, is being actively explored globally for simultaneously addressing the concerns related to improving soil fertility and mitigating climate change. Reviews on biochar, however, mainly confined to lab-scale studies analyze biochar production and its characteristics, its effects on soil fertility, and carbon sequestration. The present review addresses this gap by focusing on biochar field trials to enhance the current understanding of its actual impact on the field, w.r.t. agriculture and climate change. The review presents an overview of the effects of biochar application as observed in field studies on soil health (soil’s physical, chemical, and biological properties), crop productivity, and its potential role in carbon sequestration. General trends from this review indicate that biochar application provides higher benefits in soil properties and crop yield in degraded tropical soils vis-a-vis the temperate regions. The results also reveal diverse observations in soil health properties and crop yields with biochar amendment as different studies consider different crops, biochar feedstocks, and local climatic and soil conditions. Furthermore, it has been observed that the effects of biochar application in lab-scale studies with controlled environments are not always distinctly witnessed in corresponding field-based studies and the effects are not always synchronous across different regions. Hence, there is a need for more data, especially from well-designed long-term field trials, to converge and validate the results on the effectiveness of biochar on diverse soil types and agro-climatic zones to improve crop productivity and mitigate climate change.